Palaeo-Valleys in the Region of the Słupia River Mouth - Florek, Wacław; Rudowski, Stanisław; Szefler, Kazimierz (Quaestiones Geographicae, 2010)
Basing on results of detailed hydroacoustic research, the geological structure of the bottom to 20-22 m b.s.l. has been studied. The palaeo-Słupia palaeo-valley, buried by a thin cover of marine sands, has been recognized and determined. Some stages of valley development may be distinguished. The deposits of the oldest valley are C14 dated at ca. 21 ka BP. But in the main stage, the valley was formed by action of the subglacial and thawing glacial waters during and after the so-called Gardno Phase. Most probably this valley was connected with the Pomeranian ice margin valley. The next stages of the valley's development were related with changes of the palaeo-Słupia under conditions of the Litorina transgression. The youngest palaeo-Słupia valley is, in the authors' opinion, related with a shallow, long incision, weakly marked in the sea bottom in the central part of the studied area. Field investigations were carried out by the Department of Operational Oceanography of the Maritime Institute in Gdańsk from the r/v Dr Lubecki. A DESO 15 echosounder, Subbottom Profilers model 3010 and the X Star system were used. Eight vibrocores (core length up to 3 m) were taken from the sea bottom and three borings (10-17 m depth) were executed on the shore. Accurate positioning was obtained using the DGPS and HYDRO and Track Point Systems. All data were digitally recorded and processed.